Experience with the mother kangaroo method: mother’s perception - Antonia do Carmo Soares Campos; Mariana Pordeus Lopes Carvalho; Karla Maria Carneiro Rolim; Ana Júlia Couto de Alencar (Rev Rene)
The refl ection concerning the importance of the method mother-kangaroo for the well-being and feeling better of the binomial mother-child was what impelled us to accomplish this study which aimed to know the mothers’ perception on the mother kangaroo method. It meant to evaluate the mothers’ knowledge on the benefi ts of the mother Kangaroo method for the binomial mother-child and to identify the feeling of the mothers who experience such method. It was accomplished with 13 mothers within the months of January and February/2006 in theAssis Chateaubriand Maternity School Hospitalin Fortaleza – CE. The data were collected through semi-structured interview. In the analysis of the depositions we identifi ed the empiric categories: maternal feeling in relation to the participation in the mother kangaroo method; benefi ts of the mother kangaroo method in the mothers’ perception; diffi culty in participating in the mother kangaroo method and meaning of the mother kangaroo method. We got to the conclusion that this method makes possible the strengthening of the binomial mother-child affective bonds.